2019
DOI: 10.1111/evo.13825
|View full text |Cite
|
Sign up to set email alerts
|

Environment changes epistasis to alter trade‐offs along alternative evolutionary paths

Abstract: The fitness effect of a mutation can depend on both its genetic background, known as epistasis, and the prevailing external environment. Many examples of these dependencies are known, but few studies consider both aspects in combination, especially as they affect mutations that have been selected together. We examine interactions between five coevolved mutations in eight diverse environments. We find that mutations are, on average, beneficial across environments, but that there is high variation in their fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 45 publications
2
30
1
Order By: Relevance
“…These patterns of idiosyncratic epistasis are not due to outsized contributions from a few populations; the distributions of IM coefficients for YPD 30°C populations are different in the two assay environments across populations (Figure 3 – figure supplement 2). Overall, these results support the hypothesis that GxGxE effects underlie the differences we observe between environments (see also Hall et al 2019), though they do not rule out the possibility that differences in adaptive targets between environments may also contribute.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…These patterns of idiosyncratic epistasis are not due to outsized contributions from a few populations; the distributions of IM coefficients for YPD 30°C populations are different in the two assay environments across populations (Figure 3 – figure supplement 2). Overall, these results support the hypothesis that GxGxE effects underlie the differences we observe between environments (see also Hall et al 2019), though they do not rule out the possibility that differences in adaptive targets between environments may also contribute.…”
Section: Resultssupporting
confidence: 71%
“…The picture that emerges from our data is one in which idiosyncratic epistatic effects are largely unpredictable but have biases that often lead to correlations with background fitness. In both our own work and other studies of microbial evolution, these biases are more often towards negative epistasis: beneficial mutations tend to have negative epistatic interactions with both deleterious (Johnson et al, 2019, this study) and beneficial mutations (Chou et al, 2011; Hall et al, 2019; Karkare et al, 2021; Khan et al, 2011; Kryazhimskiy et al, 2014; Ono et al, 2017; Pearson et al, 2012; Perfeito et al, 2014; Rokyta et al, 2011; Wünsche et al, 2017).…”
Section: Discussionmentioning
confidence: 55%
“…For example, Haefeli et al and Li et al found that when there was no sodium chloride present in the system, the MIC of Ag decreased significantly for E. coli and Pseudomonas stutzeri 14,15 . Additionally, the mixed observations of resistance to Ag(I) ions within the literature could be due to fitness epistasis, that is, genetic variation within populations, coupled with differences in the external environment, both of which can dictate specific evolutionary paths and mutation effects in evolution experiments 32,33 . In our study, the decreased susceptibility of the hypermotile E. coli (+IS1) to AgNPs compared with Ag(I) ions (controlling for total Ag and Ag(I) content, see Supplementary Discussion 2) suggests a nanoparticle-specific bacterial response similar to the findings of Panacek et al 10 .…”
Section: E Coli Develops Resistance To Agnps But Not To Ag(i) Ionsmentioning
confidence: 99%
“…2013; Li and Zhang 2018; Hall et al. 2019; Lozovsky et al. 2020), there have been few formal attempts to integrate details of the environment into measurements of mutation effects and interactions.…”
mentioning
confidence: 99%